Developing Microfluidic Volume Sensors for Cell Sorting and Cell Growth Monitoring - Riordon, Jason A. (Université d'Ottawa / University of Ottawa, 2014)
Microfluidics has seen an explosion in growth in the past few years, providing researchers with new and exciting lab-on-chip platforms with which to perform a wide variety of biological and biochemical experiments. In this work, a volume quantification tool is developed, demonstrating the ability to measure the volume of individual cells at high resolution and while enabling microfluidic sample manipulations. Care is taken to maximise measurement sensitivity, range and accuracy, though novel use of buoyancy and dynamically tunable microchannels. This first demonstration of a microfluidic tunable volume sensor meant volume sensing over a much wider range, enabling the detection of ̴ 1 µm3 E.coli that would otherwise go undetected. Software was written that enables pressure-driven flow control on the scale of individual cells, which is used to great success in (a) sorting cells based on size measurement and (b) monitoring the growth of cells. While there are a number of macroscopic techniques capable of sorting cells, microscopic lab-on-chip equivalents have only recently started to emerge. In this work, a label-free, volume sensor operating at high resolution is used in conjunction with pressure-driven flow control to actively extract particle/cell subpopulations. Next, a microfluidic growth monitoring device is demonstrated, whereby a cell is flowed back and forth through a volume sensor. The integration of sieve valves allows cell media to be quickly exchanged. The combination of dynamic trapping and rapid media exchange is an important technological contribution to the field, one that opens the door to studies focusing on cell volumetric response to drugs and environmental stimuli. This technology was designed and fabricated in-house using soft lithography techniques readily available in most biotechnology labs. The main thesis body contains four scientific articles that detail this work (Chapters 2-5), all published in peer-reviewed scientific journals. These are preceded by an introductory chapter which provides an overview to the theory underlying this work, in particular the non-intuitive physics at the microscale and the Coulter principle.
Keywords: Microfluidic; Volume sensing; Coulter principle; PDMS; Soft Lithography; Photolithography; Cell sorting; Cell growth; Hydrodynamic; Electric field; Lab-on-chip